Evaluation of Occupational Health and Safety Management System (SMK3) Health Service Facilities at Puskesmas Cijagra Lama Bandung City - Susanto, Arif; Enisah, Enisah (Universitas Aisyah Pringsewu, 2020)
Health care facilities (fasyankes) are workplaces that pose risks to the safety and health of human resources (HR), patients or clients as well as their companions, visitors and the community living near the health facility. Occupational Health and Safety Management System (OHSMS) at the Community Health Center (Puskesmas) aims to efficient and continuously perform OHS at the health facilities. The purpose of this review is to evaluate the effectiveness and appropriateness of the implementation of the OHS management system, at health facilities so that they are sustainable in achieving the OHSMS goals. The method used is technical triangulation by participatory observation, in-depth interviews and document review. The results show that the Health Center of Cijagra Lama Bandung has an index of 0.8 or 80% that has fulfilled the requirements according to the Indonesian Minister of Health Regulation No. 52 year 2018 concerning Occupational Safety and Health in Health Care Facilities. Continuous improvement of OHS performance carried out for the elements of applying ergonomic principles for lifting; regular health medical check up; immunization for health workers at risk; maintenance of medical equipment; training and amount of health workers trained. Abstrak: Fasilitas pelayanan kesehatan (fasyankes) merupakan tempat kerja yang berisiko terhadap keselamatan dan kesehatan sumber daya manusia (SDM), pasien atau klien serta pendampingnya, pengujung dan masyarakat yang berada di sekitar lingkungan fasyankes. Sistem manajemen keselamatan dan kesehatan kerja (SMK3) di Pusat Kesehatan Masyarakat (Puskesmas) bertujuan untuk terselenggaranya K3 fasyankes secara optimal, efektif, efisien serta berkesinambungan. Tujuan peninjauan SMK3 ini dilakukan untuk mengevaluasi efektifitas dan kesesuaian penerapan SMK3 di fasyankes agar berkesinambungan untuk mencapai tujuan SMK3. Metode yang digunakan yaitu triangulasi teknik dengan melakukan observasi partisipatif, wawancara mendalam dan kajian dokumen. Hasil menunjukkan Puskesmas Cijagra Lama Bandung memiliki indeks sebesar 0,8 atau 80% telah memenuhi persyaratan sesuai Peraturan Menteri Kesehatan RI Indonesia Nomor 52 Tahun 2018 tentang Keselamatan dan Kesehatan Kerja di Fasilitas Pelayanan Kesehatan. Perbaikan dan peningkatan kinerja K3 yang berkelanjutan dapat dilakukan untuk elemen penerapan prinsip ergonomi untuk angkat-angkut; pemeriksaan kesehatan SDM secara berkala; imunisasi bagi SDM fasyankes yang berisiko; pemeliharaan pada peralatan medis; SDM fasyankes terlatih K3 dan jumlah SDM fasyankes yang terlatih K3.